Total productive maintenance : a conceptual framework for manufacturing performance - Harsej, Fatemeh (2011)
Since the early 1990s, the distribution of total productive maintenance (TPM) has proceeded from Japanese manufacturing systems to American manufacturers. Developed countries have considered t o maintenance as a world class strategy for increased value in manufacturing systems. To be prosperous the customer requirements, organizations have to formulate practical strategies. TPM is a strategy for the basic manufacturing functions and continuous improvement in organizations regarding to total employee involvement. It is very important to obtain suitable perspective in order to modify the organizations competitive programs. This study investigates T PM implementation and its role o n manufacturing performance in developing countries. Mos t researchers have given attention to quality, cost, delivery and flexibility as important factors for manufacturing performance measurement. Some researchers have also assessed other factors such as innovation, productivity, morale , customer satisfaction and safety. In this research , the relationship between TPM critical success factors and manufacturing performance indexes will be investigated . It requires consequential alternation of work environment culture and organization structure. A conceptual framework for verifying this relationship is suggested in this paper. It intends to analyze the relation of TPM initiatives and manufacturing performance to help in global competition . In conclusion, this paper provide s direction for research in this very important area .